Morroniside alleviates coxsackievirus B3-induced myocardial damage apoptosis via restraining NLRP3 inflammasome activation. Issue 3 (9th January 2019) - Li, Weidong; Chen, Mao; Xu, Lishuai; Lv, Zhan; Chen, Li; Li, Yiling; He, WenFen
Abstract : Coxsackievirus B3 (CVB3)-induced myocardial damage always leads to serious heart failure by inducing cardiac injury. Abstract : Coxsackievirus B3 (CVB3)-induced myocardial damage always leads to serious heart failure by inducing cardiac injury. NLRP3 inflammasome activation has been identified as a central player in the pathogenesis of CVB3-induced viral myocarditis. Therefore, restraining NLRP3 inflammasome activation has been supposed to significantly alleviate the severity of myocardial damage and improve cardiac function. Morroniside (MR), one of the main iridoid glycosides, has the ability to depress the production of reactive oxygen species (ROS) and restrain the expression of caspase-3 and -9. Of importance, ROS and caspase are essential for NLRP3 inflammasome activation in response to CVB3 infection. Therefore, in the present study, MR was selected as a model drug to alleviate CVB3-induced myocardial damage. The results of cardiac function index determination showed that abnormal indexes including mean arterial pressure, heart rate, and left ventricular systolic pressure of myocardial damage rats could be recovered by treating with MR. Such results can be further verified by histopathological evaluation, with the heart tissues of CVB3-infected rats displaying the most amount of H&E and TUNEL positive cells. The underlying mechanism by which MR improves the cardiac function was subsequently investigated. The detection of various gene levels indicated that NLRP3 inflammasome activation was inhibited by MR through down-regulating the expression of pro-inflammatory cytokines: interleukin (IL)-β and IL-18, the pivotal factors that lead to inflammatory responses. More importantly, the related genes, cardiac function indexes, and various myocardial damage markers of normal rats treated with MR did not exhibit any obvious changes compared with the control group, indicating a satisfactory biocompatibility of MR. In summary, MR holds a great potential in the alleviation of CVB3-induced myocardial damage with a negligible cytotoxicity to normal heart tissues.